User-centered development and testing of a monitoring system that provides feedback regarding physical functioning to elderly people - Vermeulen J; Neyens JCL; Spreeuwenberg MD; van Rossum E; Sipers W; Habets H; Hewson DJ; de Witte LP (Patient Preference and Adherence, 2013)
Joan Vermeulen,1 Jacques CL Neyens,1 Marieke D Spreeuwenberg,1 Erik van Rossum,1,2 Walther Sipers,3 Herbert Habets,3 David J Hewson,4 Luc P de Witte1,2 1School for Public Health and Primary Care (CAPHRI), Maastricht University, Maastricht, The Netherlands; 2Research Center for Technology in Care, Zuyd University of Applied Sciences, Heerlen, The Netherlands; 3Expertise Center for Elderly Care, Orbis Medical Center, Sittard, The Netherlands; 4Institute Charles Delaunay, Université de Technologie de Troyes, Troyes, France Purpose: To involve elderly people during the development of a mobile interface of a monitoring system that provides feedback to them regarding changes in physical functioning and to test the system in a pilot study. Methods and participants: The iterative user-centered development process consisted of the following phases: (1) selection of user representatives; (2) analysis of users and their context; (3) identification of user requirements; (4) development of the interface; and (5) evaluation of the interface in the lab. Subsequently, the monitoring and feedback system was tested in a pilot study by five patients who were recruited via a geriatric outpatient clinic. Participants used a bathroom scale to monitor weight and balance, and a mobile phone to monitor physical activity on a daily basis for six weeks. Personalized feedback was provided via the interface of the mobile phone. Usability was evaluated on a scale from 1 to 7 using a modified version of the Post-Study System Usability Questionnaire (PSSUQ); higher scores indicated better usability. Interviews were conducted to gain insight into the experiences of the participants with the system. Results: The developed interface uses colors, emoticons, and written and/or spoken text messages to provide daily feedback regarding (changes in) weight, balance, and physical activity. The participants rated the usability of the monitoring and feedback system with a mean score of 5.2 (standard deviation 0.90) on the modified PSSUQ. The interviews revealed that most participants liked using the system and appreciated that it signaled changes in their physical functioning. However, usability was negatively influenced by a few technical errors. Conclusion: Involvement of elderly users during the development process resulted in an interface with good usability. However, the technical functioning of the monitoring system needs to be optimized before it can be used to support elderly people in their self-management. Keywords: user-centered design, telemonitoring, physical functioning, community-dwelling elderly people, usability